A fuzzy grassroots ontology for improving weblog extraction - Portmann, E.; Meier, A. (Journal of Digital Information Management, 2010)
This paper presents fuzzy clustering algorithms to establish a grassroots ontology - a machine-generated weak ontology - based on folksonomies. Furthermore, it describes a search engine for vaguely associated terms and aggregates them into several meaningful cluster categories, based on the introduced weak grassroots ontology. A potential application of this ontology, weblog extraction, is illustrated using a simple example. Added value and possible future studies are discussed in the conclusion.
Keywords: Fuzzy data clustering; Information retrieval; Ontology; Search engine; Semantic web; Weblog